A framework for performative and assertive updates - Krifka, Manfred (Proceedings of Sinn und Bedeutung, 2024)
This article develops a framework for the representation of performative speech acts, in particular declarations (including explicit performatives) and assertions. It is a dynamic framework that treats these speech acts as updates of a common ground, modelled as a context set. It distinguishes between two kinds of updates: Informative updates restrict the indices of the context set by adding information, whereas performative updates change the indices, thus creating new facts. The article discusses the notion of index change in detail and presents an analysis of declarations as performative updates with a proposition concerning social facts. Assertions are specialized performative updates with a truth commitment by the speaker with implicated intention to bring about a corresponding informative update. It also discusses the various tense and aspect forms that are used to express declarations. Finally, it argues that locutionary acts can be modelled as performative updates as well and proposes a treatment of the performative marker 'hereby'.